Yeux de Lune Décroissante - Madyanis Santiago Díaz (Vernacular: New Connections in Language, Literature, & Culture, 2022)
The story, titled “Yeux de lune décroissante”, is about a French orphan boy named Théodore who lives in a beautiful rural town called Indre. He lives with his grandmother, who is very loving to everyone in the village. Théodore lets his heart guide him in everything he does, which is why he is considered a special boy who is different from others because of his transcendent, sensitive heart. He meets a couple of strangers who help him accept and understand his nature and heal from his inner suffering with their love. They form a bond that lasts beyond a lifetime.
Keywords: story; French; moon; creative